"A Great Injustice": Urban Capitalism and the Limits of Freedom in Nineteenth-Century New York City. (November 2022) - Manevitz, Alexander
Seneca Village was the largest African American landowning community in New York City until it was destroyed to build Central Park. Although it has largely been overlooked, Seneca Village reframes the early history of American capitalism at the intersection of race, freedom, and urban development, diversifying the narrative to place African American city-dwellers as actors at the center of the narrative. Real estate capitalism made Seneca Village possible, with residents using it as a means to social, political, and economic advancement, but it also destroyed Seneca Village. That paradox reveals how an emerging American urban commercial capitalism consolidated power in places Seneca Villagers could not access even when they tried. These men and women played critical, yet unacknowledged, roles as the whole nation struggled to navigate multiple visions of capitalism, their inherent inequalities, and their implications for the future.